Pragmatism-Instrumental Stream of Islamic Education and Its Relevance To Contemporary Islamic Education: Ibn Khaldun's Perspective - Marta Jaya (AMIN: International Journal of Islamic Education and Knowledge Integration, 2023)
The article discussing the Islamic education stream of pragmatism-instrumentalism according to Ibn Khaldun aims to explore the stream of pragmatism-instrumentalism in education as conceived by Ibn Khaldun's thoughts and to ascertain the relevance of Ibn Khaldun's ideas to contemporary Islamic education. The writing method employed in this paper is library research, utilizing data sources from several relevant books with titles related to philosophy, Islamic educational philosophy, and other relevant literature. The analysis utilized in this paper is descriptive-analytical analysis, which systematically examines and connects the discussed object or topic with factual phenomena to arrive at conclusions. Based on the discussion's outcomes, it is evident that Ibn Khaldun explicitly elucidates crucial elements of education in his written works. These elements encompass the educational objectives, educators and learners, teaching methods, and the educational curriculum. The concept of education derived from Ibn Khaldun's thoughts holds relevance to contemporary Islamic education practices in Indonesia today